Eosinophilic Granulomatosis with Polyangitis (EGPA) with foot drop. A rare presentation of a rare disease - Mak, Woh Wei; Masnammany, Adrian Mark; Wan Azman, Siti Sanaa; Abdullah, Hilmi (2017)
EGPA, previously known as Churg-Strauss Syndrome (CSS), is a rare, non-transmissible, medium and small vessel autoimmune vasculitis. We report a case of a 45-year-old lady whose initial presentation was left foot drop, which later on progressed to a sudden onset of vasculitic skin rashes at the background of longstanding poorly controlled bronchial asthma